Radical metabolism : a powerful plan to blast fat and reignite your energy in just 21-days - Gittleman, Ann Louise (Da Capo Lifelong, 2018)
"The New York Times bestselling author (Fat Flush series, Before the Change) is back with a new program that shares the key to a host of issues, including thyroid and autoimmune, with a practical plan for health, vibrancy, and longevity. Gut health, thyroid disorders, and autoimmune disease have all come to fore as serious health conditions that are little understood by many health professionals. Cutting-edge health pioneer Ann Louise Gittleman unlocks the secret connection to all these disorders--offering a new lifestyle and eating plan that makes you feel better. Bonus? You'll rev your metabolism and lose weight. Due to the modern Western diet and lifestyle, a large percentage of the population unknowingly suffers from bile insufficiency--meaning, their bile has become thick, sludgy and congested. A healthy gut produces an abundance of thin, freely flowing bile every day, and it must be released at the appropriate times, in appropriate amounts. In Radical Metabolism, Gittleman demonstrates how "sick bile" is often an underlying factor in thyroid dysfunction, weight gain, digestive upsets, autoimmune issues (Hashimoto's, allergies, arthritis), hormone disruption, insomnia, arthritis and chronic fatigue, and many other devastating diseases. The problem is even worse if you've had your gallbladder removed. Radical Metabolism features a 21-day healing program with basic and advanced protocols for those who still have their gallbladder, as well as for those who don't. Complete with dietary guidelines, delicious recipes, shopping lists, supplement recommendations, and an extensive resource list, Radical Metabolism offers the tools to combat chronic health conditions and offer a new lease on life"--